Alleviative Effect of Ruellia tuberosa L. on Insulin Resistance and Abnormal Lipid Accumulation in TNF-α-Treated FL83B Mouse Hepatocytes. (24th June 2021) - Chen, Hong-Jie; Ko, Chih-Yuan; Xu, Jian-Hua; Huang, Yu-Chu; Wu, James Swi-Bea; Shen, Szu-Chuan
Abstract : Type 2 diabetes mellitus (T2DM) is a chronic metabolic disease, and most patients with T2DM develop nonalcoholic fatty liver disease (NAFLD). Both diseases are closely linked to insulin resistance (IR). Our previous studies demonstrated that Ruellia tuberosa L . (RTL) extract significantly enhanced glucose uptake in the skeletal muscles and ameliorated hyperglycemia and IR in T2DM rats. We proposed that RTL might be via enhancing hepatic antioxidant capacity. However, the potent RTL bioactivity remains unidentified. In this study, we investigated the effects of RTL on glucose uptake, IR, and lipid accumulation in vitro to mimic the T2DM accompanied by the NAFLD paradigm. FL83B mouse hepatocytes were treated with tumor necrosis factor- α (TNF- α ) to induce IR, coincubated with oleic acid (OA) to induce lipid accumulation, and then, treated with RTL fractions, fractionated with n-hexane or ethyl acetate (EA), from column chromatography, and analyzed by thin-layer chromatography. Our results showed that the ethyl acetate fraction (EAf2) from RTL significantly increased glucose uptake and suppressed lipid accumulation in TNF- α plus OA-treated FL83B cells. Western blot analysis showed that EAf2 from RTL ameliorated IR by upregulating the expression of insulin-signaling-related proteins, including protein kinase B, glucose transporter-2, and peroxisome proliferator-activated receptor alpha in TNF- α plus OA-treated FL83B cells. The results of this study suggest that EAf2 from RTL may improve hepatic glucose uptake and alleviate lipid accumulation by ameliorating and suppressing the hepatic insulin signaling and lipogenesis pathways, respectively, in hepatocytes.